Shaping The World View Of Teenage Girls On The Basis Of Library And Their Education - Kochkarova Aysha Oltibayevna; Abdulazov Diorbek Otajonovich (Zien Journals, 2024)
The goal expected from the idea of attracting young people to reading, forming their spiritual and moral worldviews, forming the ability to express their personal worldviews, independent and healthy thinking, and having human qualities such as standing firm in one's opinion. is to educate the feeling of being
Keywords: outlook; reading; spirituality